Potential of Sustainable Hierarchical Zeolites in the Valorization of α‐Pinene. Issue 7 (3rd March 2015) - Nuttens, Nicolas; Verboekend, Danny; Deneyer, Aron; Van Aelst, Joost; Sels, Bert F.
Abstract In the valorization of α‐pinene, which is an important biomass intermediate derived from turpentine oil, hierarchical (mesoporous) zeolites represent a superior class of catalysts. Hierarchical USY, ZSM‐5, and beta zeolites have been prepared, characterized, and catalytically evaluated, with the aim of combining the highest catalytic performance with the most sustainable synthetic protocol. These zeolites are prepared by alkaline treatment in aqueous solutions of NH4OH, NaOH, diethylamine, and NaOH complemented with tetrapropylammonium bromide. The hierarchical USY zeolite is the most attractive catalyst of the tested series, and is able to combine an overall organic‐free synthesis with an up to sixfold activity enhancement and comparable selectivity over the conventional USY zeolite. This superior performance relates to a threefold greater activity than that of the commercial standard, namely, H2SO4/TiO2. Correlation of the obtained benefits to the amount of solid lost during the postsynthetic modifications highlights that the highest activity gains are obtained with minor leaching. Furthermore, a highly zeolitic character, as determined by bulk XRD, is beneficial, but not crucial, in the conversion of α‐pinene. The alkaline treatments not only result in a higher overall activity, but also a more functional external surface area, attaining up to four times the pinene conversions per square nanometer. The efficiency of the hierarchical USY zeolite is concomitantly demonstrated in the conversion of limonene and turpentine oil, which emphasizes its industrial potential.